ECOWAS regional integration and trans-border security management in Nigeria - Nebeife, Chigozie Joseph; Chinwuba, Michael Emeka; Onwuanibe, Jude Onyekachi (Journal of Contemporary International Relations and Diplomacy, 2022)
The Economic Community of West African States (ECOWAS) treaty was signed in Lagos on May 28, 1975, with a mandate to promote cooperation among member states and thus create a regional economic bloc. The essence of the treaty is to remove obstacles to the free movement of goods, capital, and people in the sub-region. While this integration project is noted for economic prosperity and development, it tends to have occasioned trans-border security management challenges in West Africa. Therefore, this paper examines the management of trans-border security challenges emanating from regional integration efforts in the West African sub-region. It is anchored on Neo-functional integration theory and relies on qualitative secondary data sourced through documents. This paper posits that achieving socio-economic prosperity for West Africa required eliminating certain barriers and restrictions to economic activities. However, the paper establishes that the implementation of integration programmes has thrown up new challenges for trans-border security management due to seemingly unregulated migration. It concludes that the integration programme wrapped in the ECOWAS protocol on the free movement of goods and persons has constituted bottlenecks for trans-border security management in Nigeria. It is therefore recommended among others that Nigeria’s government should strengthen its border patrol and establish a joint border patrol between Nigeria and other neighbouring countries to ensure effective trans-border security management.